Lilioceris egena (Weise) (Coleoptera: Chrysomelidae: Criocerinae) - Biological Control Agent of Air Potato Vine - F. Allen Dray Jr.; Octavio Menocal; Rosemary Murray; Eric Rohrig; Carey Minteer (EDIS)
This publication provides an in-depth profile of the air potato bulbil beetle (suggested common name), a new biological control agent of the air potato vine. It is intended for the use of interested laypersons with some knowledge of biology as well as academic audiences.